PENGARUH YOGA HAMIL MENGGUNAKAN LANTUNAN ZIKIR TERHADAP PENURUNAN TEKANAN DARAH PADA IBU PREEKLAMSIA - ros diana; lina fiitriani (J-KESMAS: Jurnal Kesehatan Masyarakat, 2021)
Preeclampsia is a disease characterized by hypertension, proteinuria, and edema that occurs during pregnancy or up to 48 hours postpartum. Pregnant yoga can lower blood pressure through stimulation of the secretion by the hormone endorphin. When the body relaxes, there is an increase in neuropeptide secretion. Yoga is proven to be able to increase 4-5 times more secretion of b-endorphins in the blood. When b-endorphins are secreted, they are captured by receptors in the hypothalamus and limbic system which have an important function in regulating emotions. This study aims to determine the effect of pregnant yoga on reducing blood pressure in preeclamptic mothers. The number of samples for this experimental study was 20 people uses quasi-experimental. Consisting of an experimental group and a control group, each of which consisted of 10 pregnant women who had preeclampsia. Based on the results of research using the Willcoxon test, in the experimental group, there was a significant effect on changes in blood pressure before and after the intervention with the experimental group's p-value for systolic blood pressure, namely p = 0.004 and diastolic p = 0.003 meaning p <0.005. So it can be concluded that there is no effect on blood pressure with a p-value> 0.005.